Comparison of Reduced Port Totally Laparoscopic-assisted Total Gastrectomy (Duet TLTG) and Conventional Laparoscopic-assisted Total Gastrectomy. Issue 6 (December 2016) - Kim, Han Byeol; Kim, Su Mi; Ha, Man Ho; Seo, Jeong Eun; Choi, Min-Gew; Sohn, Tae Sung; Bae, Jae Moon; Kim, Sung; Lee, Jun Ho
Abstract : Background: The aim of this study was to compare surgical outcomes of patients with gastric cancer undergoing reduced port totally laparoscopic-assisted total gastrectomy (duet TLTG) with those of patients undergoing conventional laparoscopic-assisted total gastrectomy (LATG). Materials and Methods: Between January 2013 and 2015, 54 patients with gastric cancer underwent LATG at the Samsung Medical Center. Duet TLTG using 3 ports was performed in 30 patients, and conventional LATG using 5 ports was performed in 24 patients. Either extracorporeal or intracorporeal anastomosis was used for esophagojejunostomy. Surgical outcomes were compared between the operation methods. Results: The operating time was similar for duet TLTG and conventional LATG [222 min (range, 163 to 287 min) vs. 233 min (range, 170 to 310 min), respectively; P =0.807]. Blood loss during surgery was also similar between duet TLTG and conventional LATG groups [100 mL (range, 50 to 400 mL) vs. 175 mL (range, 50 to 400 mL), respectively; P =0.249]. The median number of nodes dissected [duet TLTG vs. conventional LATG, 47 (20 to 67) vs. 41 (22 to 70), P =0.338] was not different between groups. Pain scores were 3.9, 3.3, and 2.9, and 3.9, 3.4, and 2.8, at postoperative days 1, 3, and 5, respectively, in the duet TLTG and the conventional LATG groups ( P =0.857, 0.659, and 0.427, respectively). Overall complication rates in the duet TLTG and conventional LATG groups were not significantly different (36.7% vs. 16.7%, P =0.103). Conclusions: Duet TLTG is an acceptable procedure with quality of lymph node dissection, including the number of dissected lymph nodes and morbidity.